2014
DOI: 10.1007/s00198-014-2909-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ibandronate therapy on serum homocysteine and leptin in postmenopausal osteoporotic females

Abstract: Our results show that ibandronate reduces serum leptin levels while it has no effect on serum homocysteine levels. Further studies are needed to explain how the decrease in serum leptin level may help in reducing the progression of osteoporosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 35 publications
3
8
0
Order By: Relevance
“…In present study, serum leptin level is considerably correlated with BMI in both groups and this result is corroborated with other studies [ 2 , 11 , 19 ]. The correlation of serum leptin with the quantity of adipose tissue in PCOS has also been supported by Kazmi et al (2013) [ 20 ].…”
Section: Discussionsupporting
confidence: 93%
“…In present study, serum leptin level is considerably correlated with BMI in both groups and this result is corroborated with other studies [ 2 , 11 , 19 ]. The correlation of serum leptin with the quantity of adipose tissue in PCOS has also been supported by Kazmi et al (2013) [ 20 ].…”
Section: Discussionsupporting
confidence: 93%
“…Recently, a study in Pakistan reported serum Hcy levels >15 µmol/l in elderly women that indicates Hcy level increases with age. 25 …”
Section: Discussionmentioning
confidence: 99%
“…Increase levels of homocysteine increases the fracture risk especially in post-menopausal females by causing oxidative damage to the bones, reducing bone quality and increasing bone resorption 10,11. Several studies have explored the relation of homocysteine with bone health in postmenopausal females,9-12 but whether physical activity also affects homocysteine levels in postmenopausal females is not completely understood.…”
Section: Introductionmentioning
confidence: 99%